Pengaruh Beban Kerja, Fasilitas, dan Pengawasan Terhadap Kepuasan Kerja PHL Pengelolaan Taman dan Ruang Terbuka Hijau DLH Kabupaten Sleman: Beban Kerja, Fasilitas, Pengawasan dan Kepuasan Kerja - Susilowati, Listri; Triwahyuni, Endang; Iman Basri, Anindita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This research aims to determine the effect of Workload, Facilities, and Supervision on Work Satisfaction of PHL Managing Parks and Green Open Spaces DLH Sleman Regency, either partially or simultaneously. This research is a quantitative study with a total of 82 respondents. Data collection techniques were carried out by means of interviews and questionnaires. The analysis technique of this research uses multiple linear regression analysis, with the help of SPSS version 23.0 for windows. The results of the partial test (t test) show that: (1) Workload has a negative and significant effect on Job Satisfaction, as evidenced by the regression coefficient of -0.124 with a significant level of 0.007<0.05; (2) Facilities have a positive and significant effect on job satisfaction, as evidenced by a regression coefficient of 0.204 with a significant level of 0.012<0.05; (3) Supervision has a positive and significant effect on job satisfaction, as evidenced by the regression coefficient of 0.430 and a significant level of 0.000 <0.05. The results of simultaneous testing (F test) of the independent variables have a significant effect on the dependent variable as evidenced by the F value of 30.271, a significant level of 0.000 <0.05. The effect of workload, facilities, and supervision on job satisfaction is shown by the adjusted R2 value of 0.520, meaning that the independent variables have an influence of 52% and the remaining 48% is influenced by other variables outside this study.